Prevalence of chronic obstructive pulmonary disease and associated factors: the PLATINO Study in São Paulo, Brazil Prevalência de doença pulmonar obstrutiva crônica e fatores associados: Estudo PLATINO em São Paulo, Brasil - Ana Maria Baptista Menezes; José Roberto Jardim; Rogelio Pérez-Padilla; Aquiles Camelier; Fernanda Rosa; Oliver Nascimento; Pedro Curi Hallal (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
Chronic obstructive pulmonary disease (COPD) is now a major public health concern; deaths attributable to COPD in Latin America have increased by 65.0% in the last decade. This study was aimed at evaluating COPD prevalence and associated factors in adults (> 40 years) living in Greater Metropolitan São Paulo, Brazil. The study is part of the Proyecto Latinoamericano de Investigación en Obstrucción Pulmonar (The PLATINO Project), a multi-center survey on COPD burden in Latin America, with São Paulo as the first center where the project has been carried out. A population-based sample was selected in multiple stages. Spirometry tests were performed in each subject pre- and post-bronchodilator and COPD was mainly defined as the ratio of forced expiratory volume to forced vital capacity below 70.0% (fixed ratio definition). Other spirometric criteria were also used for the diagnosis of COPD. COPD prevalence was 15.8% (95%CI: 13.5-18.1) using the fixed ratio definition. COPD was positively associated with age and smoking and inversely with body mass index. Utilization of different COPD spirometry criteria resulted in different percentages of COPD, but similar associated factors. A doença pulmonar obstrutiva crônica (DPOC) é hoje um grande desafio para a saúde pública; as mortes atribuídas a DPOC na América Latina aumentaram 65,0% na última década. Avaliou-se a prevalência de DPOC e fatores associados em uma população adulta (> 40 anos) da grande área metropolitana de São Paulo, Brasil. Esse estudo faz parte do Proyecto Latinoamericano de Investigación en Obstrucción Pulmonar (Projeto PLATINO), um estudo multicêntrico sobre DPOC em grandes cidades da América Latina, tendo sido São Paulo o primeiro centro onde o projeto se realizou. O estudo foi transversal de base populacional e amostragem em múltiplos estágios. Os indivíduos realizaram espirometria, e DPOC foi basicamente definida como a razão entre o volume expiratório forçado em um segundo (VEF1) e a capacidade vital forçada (CVF) abaixo de 70,0% (relação fixa). Outros critérios espirométricos foram também utilizados para o diagnóstico de DPOC. A prevalência de DPOC foi de 15,8% (IC95%: 13,5-18,1) usando-se o critério mencionado acima. DPOC associou-se positivamente com idade e tabagismo e inversamente com o índice de massa corporal. O uso de diferentes critérios espirométricos acarretou mudanças na freqüência de DPOC, mas não nos fatores associados.